2011
DOI: 10.1109/tip.2011.2121085
|View full text |Cite
|
Sign up to set email alerts
|

A Closed-Form Approximation of the Exact Unbiased Inverse of the Anscombe Variance-Stabilizing Transformation

Abstract: We presented an exact unbiased inverse of the Anscombe variance-stabilizing transformation in [M. Mäkitalo and A. Foi, "Optimal inversion of the Anscombe transformation in low-count Poisson image denoising," IEEE Trans. Image Process., vol. 20, no. 1, pp. 99-109, Jan. 2011.] and showed that when applied to Poisson image denoising, the combination of variance stabilization and state-of-the-art Gaussian denoising algorithms is competitive with some of the best Poisson denoising algorithms. We also provided a MAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 3 publications
1
46
0
Order By: Relevance
“…Moreover, we demonstrate that our approach leads to state-of-the-art results. This paper generalizes our earlier work [3], [4], in which we presented an exact unbiased inverse of the Anscombe transformation [5] and showed its importance in obtaining accurate denoising results for the case of pure Poisson noise.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Moreover, we demonstrate that our approach leads to state-of-the-art results. This paper generalizes our earlier work [3], [4], in which we presented an exact unbiased inverse of the Anscombe transformation [5] and showed its importance in obtaining accurate denoising results for the case of pure Poisson noise.…”
Section: Introductionsupporting
confidence: 77%
“…We have generalized our earlier work [3], [4] by proposing an exact unbiased inverse of the generalized Anscombe transformation for Poisson-Gaussian noise. We showed that the denoising performance associated with this inverse, in conjunction with a state-ofthe-art Gaussian noise removal algorithm, is competitive with that of a state-of-the-art algorithm designed specifically for the removal of Poisson-Gaussian noise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In digital cameras, the two major sources of noise during the acquisition process are the thermal agitation, which produces an almost white and Gaussian noise, and the discrete nature of light, which is behind the photon shot noise, modeled as a Poisson variable (for a complete description of the sources of noise in a digital camera, see [2]). Stabilizing the noise variance by a generalized Anscombe transform [13] results in a noise model well approximated by a white Gaussian noise ε ∼ N (0, σ 2 I m ). The vast majority of works on image denoising focus on this simplified model and it is also our assumption in this chapter.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate filter and algorithm were required to reduce the noise in images. Although the median filter based on median value in the designated area was frequently used in the medical imaging field, different techniques for the noise reduction have been recently developed [1][2][3] [4][5][6]. Especially, Anscombe noise reduction technique is useful in various inverse problems with Poisson noise contamination.…”
Section: Introductionmentioning
confidence: 99%